2019
DOI: 10.1007/s13762-019-02284-9
|View full text |Cite
|
Sign up to set email alerts
|

The microbiology contaminants and microclimate parameters in the nursery building

Abstract: The indoor microclimate quality is an important factor affecting the human body. Inappropriate microclimate parameters and air pollutants can cause health problems or even be life-threatening. In addition, it can reduce work productivity and learning efficiency. In the article, the analysis of the rooms in the nursery building ventilated by a mechanical system equipped with air ionizers was conducted. The results of research were compared with the research results for rooms of the same type, but equipped with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Healthy indoor air quality can be improved by avoiding overcrowding, good system design [47,57], and suitable construction materials [29]. Density in the room causes poor indoor air quality, especially for increased temperature, humidity, and carbon dioxide [58]. Monitoring indoor air quality is needed to reduce symptoms of sick buildings, especially for parameters: temperature, humidity, carbon monoxide, carbon dioxide, and luminosity [59].…”
Section: Microbiological Contamination Indexmentioning
confidence: 99%
“…Healthy indoor air quality can be improved by avoiding overcrowding, good system design [47,57], and suitable construction materials [29]. Density in the room causes poor indoor air quality, especially for increased temperature, humidity, and carbon dioxide [58]. Monitoring indoor air quality is needed to reduce symptoms of sick buildings, especially for parameters: temperature, humidity, carbon monoxide, carbon dioxide, and luminosity [59].…”
Section: Microbiological Contamination Indexmentioning
confidence: 99%
“…One of the ways to deal with the sick building syndrome is ensuring proper ventilation within buildings. This issue was studied by the author [8] as well as other researchers (e.g. [9]) and seems to be the answer to a number of problems related to indoor microclimate.…”
Section: Introductionmentioning
confidence: 98%
“…Several prior studies have demonstrated that the microbial characterization depends on the indoor air environment and will differ greatly in season, time, ventilation, and location (Fujiyoshi, Tanaka and Maruyama, 2017). A previous study has reported that an indoor air temperature exceeding 25 o C can cause an increase in fungi growth (Zender-Świercz et al, 2019). It is also suggested that there is a correlation between the amount of fungi and the indoor air temperature (Stojanović Bjelić, Ilić and Farooqi, 2020).…”
Section: Introductionmentioning
confidence: 99%